Social Security of Migrant Workers from Ukraine in EU Member States - Zhuravel, Valeriy O.; Karpushova, Olena V.; Bielousov, Volodymyr D.; Platonova, Hanna; Dyachenko, Olha A. (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2023)
Labor migration is becoming a growing trend in the modern labor market. It has positive aspects, such as the redistribution of labor and the increase in human capital efficiency. However, along with other elements of a flexible labor market, labor migration can also threaten workers' social protection. The study of social security issues helps to assess the extent to which these workers have access to the necessary social services and benefits, which contribute to their well-being and encourage further contribution to the economy. The primary research method is system analysis, which considers social security as a complex system that includes various components, interrelationships, and influences. The research results found that EU legal acts are equality-oriented and give EU member states the opportunity to set their own rules for migrants coming from third countries. As the economic and social situation in different EU countries differs, member states are trying to preserve the shared values and principles of the Union while protecting their markets from additional social obligations related to the employment of third-country nationals. The priorities of Ukraine's migration policy are to protect citizens' rights and interests abroad and coordinate social security systems with recipient countries of Ukrainian labor migrants.